Analisis Butir Soal Ujian Sekolah Mata Pelajaran Ilmu Pengetahuan Sosial Kelas VI SDN Kota Bengkulu Tahun Pelajaran 2019/2020 - yusnia yusnia; Badeni Badeni; puspa djuwita (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2021)
This study aims to describe the proportion of the cognitive level, affective level, logically and empirically the question items on the School Examination in Social Sciences subjects for the sixth grade students of SDN Kota Bengkulu for the 2019/2020 academic year. This type of research is descriptive research. The subjects in this study were students of class VI SDN 53, SDN 18, and SDN 29 Bengkulu City. The object of this research is the suitability of the questions and answer keys, answers to the school exam. The research instrument used is in the form of a document in the form of a cognitive level report analysis sheet, and an affective level report analysis sheet, questions and answer keys, answers to school exams. The data analysis uses the population level cognitive affective level on the items analyzed, the percentage is calculated, as well as descriptive analysis of material aspects, construction, and language by asking for validation from analysis experts/ experts using Aiken V. The results show that: 1) The proportion of cognitive levels, including levels understand (C2) as many as 14 items (35%), the level of implementing (C3) is 9 items (22.50%), the level of analysis (C4) is 15 items (37.50%), and the level of understanding (C5) as many as 2 items (5%); 2) The proportion of the affective level, including the response level (A2) as many as 1 item (2.5%), the respect level (A3) as many as 3 items (7.5%) and the organizing level (A4) as many as 3 questions (7, 5%); 3) the quality of the items logically based on the results of the validation of material aspects, construction, and language. 40 multiple choice test items show the information displayed in the range> 0.8 with the category "very valid" in accordance with the principles of assessment, namely fair, open, comprehensive and continuous, systematic, reference criteria, and accountable; and 4) The quality of the items empirically, the validity results show that 39 items are valid and 1 item is invalid, the reliability test results are 0.735 so it can be interpreted that these items have a high level of reliability, the results of the difficulty level test show that 15 items Medium category questions (37.5%) and 24 items in the easy category (60%), the results of the distinguishing power test showed that 5 items were in the good category (12.5%), 34 items were in the sufficient category (85%) in accordance with the principle Output, namely valid, objective, open, systematic, and based on criteria. Thus it can be denied that the quality of the School Examination items in the Social Sciences subject grade VI SDN Kota Bengkulu for the 2019/2020 academic year is good in terms of the statement of cognitive level, affective level, quality based on logical and empirical tests.